Prevalencia de diferentes tipos de violencia en usuarias del sector salud en México Gender violence prevalence in female users of health services in Mexico - Gustavo Olaiz; Rosalba Rojas; Rosario Valdez; Aurora Franco; Oswaldo Palma (Instituto Nacional de Salud Pública, 2006)
OBJETIVO: Identificar la prevalencia de la violencia contra las mujeres en usuarias del sector salud en México. MATERIAL Y MÉTODOS: En 2003 se levantó la Encuesta Nacional sobre Violencia contra las Mujeres 2003 (ENVIM 2003) en usuarias de los servicios médicos de primer y segundo nivel. El esquema de muestreo se basó en una muestra probabilística estratificada en dos etapas: a) de un listado de unidades médicas elegibles, se seleccionaron aquellas con probabilidad proporcional al número de consultorios de la unidad; b) mediante muestreo sistemático se seleccionó a mujeres de 15 años y más que acudieron a la unidad médica. Se realizó un análisis univariado y posteriormente uno bivariado. RESULTADOS: Participaron 26 042 mujeres de 15 a 92 años de edad. La media de edad fue de 35.8 años. La violencia física durante la niñez, notificada, fue de 42.2%. Sólo 7.8% de las mujeres respondieron afirmativamente a la pregunta general de violencia de pareja. Sin embargo, al aplicar la escala de violencia, la prevalencia de cualquier tipo de violencia en los últimos 12 meses fue de 21.5%. El tipo de violencia más frecuente fue la psicológica (19.6%). De las mujeres que tuvieron antecedente de embarazo, 14.1% señalaron violencia y 4.4% refirieron haber sido golpeadas en el abdomen. La prevalencia de violencia sexual fue de 17.3% y cerca de la mitad de este porcentaje la padecieron antes de los 15 años de edad. La violencia se presenta en mayor prevalencia en las usuarias de la SSA, entre las de menor escolaridad, entre aquellas que no viven en casa propia y entre las que viven en mayor hacinamiento. CONCLUSIONES: La identificación y la medición de la violencia constituyen un fenómeno complejo en consideración a los diversos tipos de violencia que existen y a la manera en que las mujeres mismas la perciben y la notifican. La violencia es un problema importante de salud, tanto por la alta prevalencia como por sus consecuencias inmediatas y acumulativas sobre la salud. Los resultados indican la necesidad urgente de prevenir y atender este problema. OBJECTIVE: To identify the prevalence of violence against females among those who are health service beneficiaries in Mexico. MATERIAL AND METHODS: The National Survey on Violence against Women (ENVIM, per its Spanish abbreviation) was applied in 2003 to female users of public primary and secondary health care services. The sampling framework was based on a stratified, probabilistic sample in two stages. First the health care units were selected with probability proportional to the number of physicians' offices in the unit, from a list of possible care units. Second, women 15 years and older who sought care at the health care unit were selected for participation in the study through systematic sampling. Univariate analysis and then bivariate analysis were carried out on the data collected with a questionnaire. RESULTS: The sample included 26 042 women between 15 and 92 years of age, with a mean age of 35.8 years. Physical violence during childhood was reported by 42% of the women. Only 7.8% answered yes to a general question about whether they experienced domestic partner violence, but 21.5% reported experiencing violence of any type during the last 12 months as measured by a scale including specific acts of psychological, economic, physical and sexual violence. The most frequently reported type of violence was psychological (19.6%). Of the women who had been pregnant, 14.1% reported having experienced violence during pregnancy, and 4.4% reported being hit in the abdomen. The prevalence of sexual violence was 17.3% and close to half reported being victims of this type of violence before age 15. Higher prevalence of violence was found among women with lower levels of formal education, living in a rented home, in areas with higher overcrowding indices, and users of Ministry of Health care services. CONCLUSIONS: Identifying and measuring violence is complex, given the diverse types of violence and how they are perceived and therefore reported by women themselves. This is an important public health problem, in view of the high frequency observed in this study and the immediate implications. These findings indicate the urgent need for interventions to prevent and treat violence.